Characteristics of the microbiome in patients with symptomatic uncomplicated colonic diverticular disease in the central region of Ukraine - A. E. Dorofieiev; H. A. Dorohavtseva (Zaporožskij Medicinskij Žurnal)
The aim of the study was to analyze the age structure, correlation with body mass index in patients with symptomatic uncomplicated diverticular disease (SUDD) in the central region of Ukraine. To reveal the prevalence of left-sided, right-sided or total diverticular lesions of the large intestine, to evaluate the microbiota composition, to identify peculiarities of the enterotype.